Analisis Perbandingan User Experience pada Website dan Aplikasi Mobile Shopee Menggunakan UEQ - Sandi Prasetyaningsih; Salsa Putri Nabila Muchtar (Sekawan Institut, 2023)
In the midst of technological developments that are always advancing, the internet is one of the things that makes life easier. The internet itself produces products that are useful for daily activities, for example websites and applications. These two products have many types of usage categories, one of which is e-commerce. E-commerce (electronic commerce) provides a different shopping experience for consumers. One of the e-commerce that is developing in Indonesia is Shopee. Shopee has 2 (two) versions, a mobile application and a website. In this case, of course, the layout of the user interface provided is definitely different. Different layouts certainly provide a different user experience. The purpose of this research is to analyze and evaluate user experience and to find out user perceptions and interaction problems experienced by users when using mobile applications and the Shopee website. This study uses 2 (two) research methods, namely user experience questionnaire and Focus Group Discussion. The results of this analysis show that the mobile application and Shopee website have significant values ??for each parameter. Both Shopee platforms only have 4 (four) of the 6 (six) parameters that reach 0.8. This shows that the Shopee mobile application and the Shopee website have their own strengths and weaknesses in terms of user experience.